The Influence of Corporate Culture Dimensions on Organizational Commitment: Case Study of Two Government Organizations in Alor Setar, Kedah Darul Aman - Eliy Nazira, Mat Nazir (2012)
The purpose of this study was to examine the influence of four dimensions of corporate culture,namely,communication, teamwork,training and development, and reward and recognition on employees’ organizational commitment within two government organizations, namely, Kedah State Development Corporation (PKNK) and Alor Setar City Council (MBAS) located in Alor Setar, Kedah Darul Aman. Despite extensive research on corporate culture, very little empirical research has examined this area of study, especially for public sectors in Kedah. 300 set of questionnaires was distributed to both organizations and 218 sets of completed questionnaires have returned. Regression analyses were employed to test the research hypotheses. The results of this study revealed that communication, training and development, reward and recognition, had positively influences employees’ commitment. This study contributes to a better understanding of the influence of corporate culture on organizational commitment among employees within the government organization in Kedah.